Drugs of Physical Harm in Pregnancy: Nature Vs Nurture-A Silent Battle - Sunil Kumar Pandey, Deepanjana Dass (Journal of Applied Pharmaceutical Science)
Drug misuse is a major social, legal, and public-health challenge in the modern world. Drug misuse affects society, family, individual users and offsprings. Using illicit substances during pregnancy is common. A study in UK inner-city clinic demonstrated 16% of the women had taken one or more illicit substances. Screening newborns in a high-risk urban population of USA revealed 44% of 3010 babies tested positive for opiates, cocaine or cannabis. Maternal drug abuse jeopardize maternal health and results in poor foetal outcome. Here we will discuss mainly about antenatal, postnatal, foetal consequences and management of maternal drug abuse. Four drugs i.e Heroin, Methadone, Barbiturates and Cocaine have been selected because they have maximum propensity to cause physical harm. These drugs easily cross the placenta and pass into breast milk, affecting the baby and are so addictive that the unborn baby can become dependent on the drug. Women abusing these drugs during pregnancy can experience memory loss, irritability, changes in alertness and can increase the risk of antepartum haemorrhage, preterm birth, low birth weight, neural tube defects, cleft palates, cardiac defects and microcephaly. Cocaine may cause an unborn baby to die or experience stroke, which can result in irreversible brain damage as they have not yet developed the enzyme that inactivates it. Neonatal withdrawal symptoms have also been reported in infants. Drug use in pregnancy is a potentially complex bio-psychosocial problem and is best managed through careful assessment leading to a care plan that is implemented by a multidisciplinary team.
Keywords: Drugs,Physical harm,Pregnancy,Misuse,Heroin,Street methadone,Barbiturates,Cocaine.